Climate change adaptation and the agricultural sector in South American countries: Risk, vulnerabilities and opportunities - Taboada, Miguel Ángel; Costantini, Alejandro Oscar; Busto, Mercedes; Bonatti, Michelle; Sieber, Stefan (Sociedade Brasileira de Ciência do Solo, 2021)
South America covers a vast area with diverse climates and landscapes, with high participation in the global production of food and fibers. It is crucial to understand the risks, vulnerabilities, and opportunities that climate change brings to this region. We analyzed the increasing tension between agribusiness models and smallholder models, the risks, opportunities, and main adaptation measures that can be adopted in the agricultural sector of the South American countries facing climate change. This study is a review of adaptation actions in the agricultural sector for the different regions of South America. Vulnerability exists, firstly, because rural populations are exposed in many of the countries, often with high rates of poverty and low rates of socioeconomic development. Concerning the adaptation measures already taken, there are numerous cases of interventions by national, provincial, and municipal states for planned measures. Farmers are very active in adopting autonomous measures. Many adaptation measures show co-benefits with climate change mitigation or the prevention of land degradation and desertification, but other adaptation measures do not go in this direction. In the forthcoming times, the region’s rich natural resources are going to be subjected to strong market pressures and climate change threats. It is key to generate strategies for the care of these resources for their permanence for future generations.
Keywords: food production systems; risk areas; poverty rates; autonomous measures; government measures